Latvijas apģērbu modes zīmolu komunikācija sociālajos tīklos - Rutka, Evita (Latvijas Universitāte, 2015)
Bakalaura darbs „Latvijas apģērbu modes zīmolu komunikācija sociālajos tīklos” ir izstrādāts ar mērķi, lai noskaidrot kā Latvijas apģērbu modes zīmoli komunicē ar saviem patērētājiem sociālajos tīklos, cik šiem zīmoliem šī komunikācija ir svarīga un kā šo komunikāciju vērtē modes zīmolu sekotāji. Darbā veikta teorētisko nostādņu apkopošana, bet darba metodoloģijā apskatītas izmantotās pētniecības metodes. Empīriskajā daļā tiek aprakstīti pētījuma rezultāti, bet darba beigās tiek veikti secinājumi. Darba rezultātā ir secināts, ka Latvijas apģērbu modes zīmoliem komunikācija sociālajos tīklos ir diezgan svarīga, bet šo zīmolu sekotāji šo komunikāciju vērtē diezgan neitrāli Atslēgas vārdi: Latvijas apģērbu modes zīmoli, Latvijas mode, modes patērētāji, sociālie tīkli, zīmolu komunikācija sociālajos tīklos

Bachelor's thesis: "Latvian fashion clothing brands’ communication in social networks" is developed with the purpose to find out how are Latvian apparel fashion brands communicating with their consumers, how important is this communication to them and also how the communication is viewed by the consumers. In the research the theoretical approaches are gathered. The methodlogy of the thesis concentrates itself on the used research methods. The empirical part of the research shows the concluded results. At the end of the research conclusions are made. In the result of the research it is concluded that the latvian apparel brand managers concider the communication in social media with their consumers as important but the consumers consider it as neutral. Key words: Latvian apparel brands, Latvian fashion, fashion consumers, social networks, brand communication in social networks. ANNOTATION Bachelor's thesis: "Latvian fashion clothing brands’ communication in social networks" is developed with the purpose to find out how are Latvian apparel fashion brands communicating with their consumers, how important is this communication to them and also how the communication is viewed by the consumers. In the research the theoretical approaches are gathered. The methodlogy of the thesis concentrates itself on the used research methods. The empirical part of the research shows the concluded results. At the end of the research conclusions are made. In the result of the research it is concluded that the latvian apparel brand managers concider the communication in social media with their consumers as important but the consumers consider it as neutral. Key words: Latvian apparel brands, Latvian fashion, fashion consumers, social networks, brand communication in social networks. ANNOTATION Bachelor's thesis: "Latvian fashion clothing brands’ communication in social networks" is developed with the purpose to find out how are Latvian apparel fashion brands communicating with their consumers, how important is this communication to them and also how the communication is viewed by the consumers. In the research the theoretical approaches are gathered. The methodlogy of the thesis concentrates itself on the used research methods. The empirical part of the research shows the concluded results. At the end of the research conclusions are made. In the result of the research it is concluded that the latvian apparel brand managers concider the communication in social media with their consumers as important but the consumers consider it as neutral. Key words: Latvian apparel brands, Latvian fashion, fashion consumers, social networks, brand communication in social networks.
Latvian fashion clothing brands’ communication in social networks
Keywords: Komunikācijas zinātne; Latvijas apģērbu modes zīmoli; Latvijas mode; modes patērētāji; sociālie tīkli; zīmolu komunikācija sociālajos tīklos